2009
DOI: 10.1177/0011128709331790
|View full text |Cite
|
Sign up to set email alerts
|

What a Girl Wants, What a Girl Needs

Abstract: Most arrests among girls are attributable to status offenses and property crimes; however, the number of girls arrested for assault and other violent crimes is increasing. Although arrest patterns among girls may be changing, the way the system responds has not. Correctional programs have almost always been designed with the male offender in mind—ignoring the needs of at-risk and delinquent girls. The paucity of gender-specific programming might have seemed acceptable in the past; however, academics and practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…Values that oftentimes accompany conventional family life then became some of the most reoccurring themes: our study revealed that the needs for being heard out, loved, understood, cared for, and supported were most prevalent, which were findings supporting other research (e.g., Belknap et al, 1997;Chesney-Lind et al, 2008). Our findings also suggested that CSEC survivors did feel that delinquent peers can encourage other types of delinquent behavior through social learning (Bao et al, 2014;Garcia & Lane, 2013). Social learning seems to be the case especially when CSEC youth are grouped with detainees that have participated in criminal activity voluntarily.…”
Section: Discussionsupporting
confidence: 79%
“…Values that oftentimes accompany conventional family life then became some of the most reoccurring themes: our study revealed that the needs for being heard out, loved, understood, cared for, and supported were most prevalent, which were findings supporting other research (e.g., Belknap et al, 1997;Chesney-Lind et al, 2008). Our findings also suggested that CSEC survivors did feel that delinquent peers can encourage other types of delinquent behavior through social learning (Bao et al, 2014;Garcia & Lane, 2013). Social learning seems to be the case especially when CSEC youth are grouped with detainees that have participated in criminal activity voluntarily.…”
Section: Discussionsupporting
confidence: 79%
“…Training females in socio-cognitive skills would be aimed to help them cope not only with interpersonal problems in general terms, but specifically with abandonment, neglect, and IPV. Adding these contents might increase motivational engagement, readiness for treatment and, consequently, behavioral change of young female offenders (Garcia & Lane, 2013;McMurran & Ward, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, most approaches agree that family and intimate relations play an important role in the origin of female delinquency (Garcia & Lane, 2013). Static risk factors pertaining to the family domain are more common in girls than in boys.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted, the rationale for much of the gender-responsive programming is based on neurophysiological and socio-emotional, individual-level, as well as systemiclevel differences that have been identified between boys and girls (the majority of these studies assume a gender binary which, again, the authors do not) (Bennett et al 2005;Hubbard and Matthews 2008). Garcia and Lane (2013) note that for the most part, the reasons girls get into trouble are different than for boys and that these reasons (substance use; relationships/sex, STDs, and pregnancy; dysfunctional families/running away; physical, emotional, and sexual abuse; school disengagement and truancy; and delinquent peers) should match the services they most desire and need (mentoring by caring respectful staff, practical life skills, clinical services for their abuse histories, mental health symptoms, and substance use).…”
Section: Improve Gender-and Culturally Responsive Programmingmentioning
confidence: 99%